Exploring educational needs of young farmers in precision agriculture in Serres, Greece, and the perspective of innovative agricultural educational programs - Kountios, Georgios; Bournaris, Thomas; Papadavid, George; Michailidis, Anastasios; Papadaki-Klavdianou, Afroditi (My University, 2018)
This study attempts to seek the main educational needs of young farmers regarding the use of precision agriculture in Serres, Greece. The main methodological analysis includes a descriptive analysis of frequencies, a categorical principal components analysis (CaPCA) and a categorical regression (CatReg). The most interesting result of this research is the fact that young farmers in Serres are well informed about precision agriculture. On the other hand, the respondents showed an increased level of educational needs and a clear desire to receive further agricultural education related to precision agriculture. Plus, the desired education seems to be influenced by their different social and agricultural characteristics, which can lead to the configuration of suitable educational programs, adapted in the particularities of each category. This ascertainment can lead to creating appropriate educational programs adapted to particularities of each category, in order to confront the multifarious demands related to information and training issues.
Keywords: Agricultural education; Educational needs; Greece; Precision agriculture; Young farmers